Пророк. Голос ангела: роман / Андрей Воронин - Воронин Андрей Николаевич (Современный литератор, 2002)
Экземпляры: (20181016) / Инвентарный номер: 43213 / Цена: 32.00 / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 28 / ББК: 84(2Рос=Рус)6-4